2009
DOI: 10.1121/1.3158600
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of auditory-motor representations to subtle changes in auditory feedback while singing

Abstract: Singing requires accurate control of the fundamental frequency ͑F0͒ of the voice. This study examined trained singers' and untrained singers' ͑nonsingers'͒ sensitivity to subtle manipulations in auditory feedback and the subsequent effect on the mapping between F0 feedback and vocal control. Participants produced the consonant-vowel /ta/ while receiving auditory feedback that was shifted up and down in frequency. Results showed that singers and nonsingers compensated to a similar degree when presented with fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 38 publications
(70 reference statements)
5
29
1
Order By: Relevance
“…Certainly, vocal training alters audio-vocal interactions (Burnett & Larson, 2002;Jones & Keough, 2008;Keough & Jones, 2009;Zarate, Wood, & Zatorre, 2010;Zarate & Zatorre, 2005. We found limited but relevant evidence that vocal training was associated with attenuated pitch-shift amplitudes for simple vowel production and under the T12 condition.…”
Section: Vocal Trainingmentioning
confidence: 54%
“…Certainly, vocal training alters audio-vocal interactions (Burnett & Larson, 2002;Jones & Keough, 2008;Keough & Jones, 2009;Zarate, Wood, & Zatorre, 2010;Zarate & Zatorre, 2005. We found limited but relevant evidence that vocal training was associated with attenuated pitch-shift amplitudes for simple vowel production and under the T12 condition.…”
Section: Vocal Trainingmentioning
confidence: 54%
“…Gradual modification of speakers' feedback is a paradigm known as sensorimotor adaptation, which has been employed by a number of research groups over the years. These types of experiments have been shown to yield a robust, consistent response in which speakers compensate over time for the gradually increased manipulations in f o : If f o is experimentally increased, speakers respond by lowering their f o over time (Jones & Keough, 2008;Jones & Munhall, 2000Keough & Jones, 2009;Patel, Niziolek, Reilly, & Guenther, 2011). As evidenced by short-term maintenance of the response after removal of the shift, speakers seem to temporarily update (i.e., adapt) their motor programs.…”
mentioning
confidence: 99%
“…However, it should be noted that all the participants in this study were non-singers. Given the potential differences in vocal motor control between singers and non-singers (Keough and Jones, 2009), the results of this study should not be applied to trained singers without further testing. Also, it would be interesting to test if the lack of carry-over effects in different vocalization contexts applies to formant control as well as F0 control.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that there may be differences between singers, who are highly trained in vocal control, and non-singers when they adapt to changes in F0 (Jones and Keough, 2008;Keough and Jones, 2009). There are several other special populations who are of interest in studies of sensory-motor adaptation, including Parkinson patients, amusics, schizophrenics (who may have a disruption in the signals sent to auditory cortex to identify speech as self-generated; Ford and Mathalon, 2004), and children at various stages of development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation